Using Microsoft Word 2010. Part 3 - Megel, Yu. Ye.; Kovalenko, S. M.; Chaly, I. V.; Mikhnova, O. D.; Chala, O. I. (Kharkiv Petro Vasylenko National Technical University of Agriculture, 2015)
Methodological guidelines are intended to assist students in studying Informatics in English, both in the classroom and individually.
Keywords: methodological guidelines; information technology; Microsoft Word; computer technologies